2022
DOI: 10.3389/fnagi.2022.933893
|View full text |Cite
|
Sign up to set email alerts
|

ATP1A3 mutation in rapid-onset dystonia parkinsonism: New data and genotype-phenotype correlation analysis

Abstract: BackgroundRapid-onset dystonia parkinsonism (RDP) is a rare disease caused by ATP1A3 mutation with considerable clinical heterogeneity. Increased knowledge of RDP could be beneficial in its early diagnosis and treatment.ObjectiveThis study aimed to summarize the gene mutation spectrum of ATP1A3 associated with RDP, and to explore the correlation of ATP1A3 variants with RDP clinical phenotypes.MethodsIn this study, we reported two RDP patients from a family with a novel inherited ATP1A3 variant. Then, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the ATP1A3 A813V mutation, the initial alanine was changed to valine. Crystallography showed that the side chain of valine was significantly larger than that of alanine, which changed the shape of the ATP1A3 protein and reduced its biological activity [51]. (i) GCH1 (guanosine triphosphate cyclohydrolase I gene-biosynthesis of neurotransmitters) The GCH1 gene codes for the expression of the enzyme GTP cyclohydrolase 1.…”
Section: The Genetic Background Of Dystoniamentioning
confidence: 99%
“…In the ATP1A3 A813V mutation, the initial alanine was changed to valine. Crystallography showed that the side chain of valine was significantly larger than that of alanine, which changed the shape of the ATP1A3 protein and reduced its biological activity [51]. (i) GCH1 (guanosine triphosphate cyclohydrolase I gene-biosynthesis of neurotransmitters) The GCH1 gene codes for the expression of the enzyme GTP cyclohydrolase 1.…”
Section: The Genetic Background Of Dystoniamentioning
confidence: 99%